PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) BERNUANSA KONTEKSTUAL PADA SUB POKOK BAHASAN KUBUS DAN BALOK UNTUK SMPKELAS VIII SEMESTER GENAP - Afisa, Nurul; Sugiarti, Titik; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2013)
Abstract.The characteristics of Missouri Mathematics Project (MMP) learning model based oncontextual teachingare reviewing, developing, excercise control, individual excercise, and project. The research aimsto know the process and result of development of learning materialsof Missouri Mathematics Project (MMP) Learning Model based on Contextual For Cube and Cuboid Topic At Eight Grade Of Junior High School in Second Semester. Learning materialsdevelopment model refers to 4D Thiagarajan models. This research has product namely lesson plan, student book, worksheet, and evaluation test. Based on validation process and tryout the learning sets can be concluded that the learning sets had been appropriate with validate, practice, and effective criteria. Key Words:Missouri Mathematics Project (MMP) Learning Model,Contextual, Cube and Cuboid.